Evaluasi Dan Optimasi Pompa Electrical Submersible Pump Di Sumur JVT-20 Pada Lapangan X - Josep V Talahaturuson; Purnomosidi Purnomosidi; Berthy Pelasula Pelasula (Department of Mechanical Engineering, 2023)
Electrical Submersible Pump (ESP) is a multilevel pump that is inserted into the well, by being immersed in the fluid and driven by an electric motor to lift the fluid from the well to the surface. The ESP currently used in the JVT-20 well is REDA A400 type ESP with 18 - 50 Stage, 60 Hz with a pump capacity of 200 - 500 BFPD. The JVT-20 well experienced a decrease in production rate so that only 150 BFPD was produced with a 75% water cut. The JVT-20 well's inflow performance relationship curve has a maximum flow rate of 214,286 BFPD, therefore optimization efforts are being made so that the daily production capacity of the JVT-20 well approaches the maximum flow rate of the well. The optimization was carried out by replacing the installed pump with a new pump type, namely ODI W2, with 110 stages, pump size 4.3 HP 60 Hz, with a production flow rate of 171.27 BFPD approaching the targeted flow rate for the JVT-20 well and pump efficiency of 45%. Keywords: Optimization, Electrical submersible Pump, Evaluation, Well, JVT-20 Â